How patients' psycho‐social profiles contribute to decision‐making in epilepsy surgery: A prospective study. Issue 3 (18th January 2023) - Hohmann, Louisa; Bien, Christian G.; Holtkamp, Martin; Grewe, Philip
Abstract: Objective: Identifying factors associated with surgical decision‐making is important to understand reasons for underutilization of epilepsy surgery. Neurologists' recommendations for surgery and patients' acceptance of these recommendations depend on clinical epilepsy variables, for example, lateralization and localization of seizure onset zones. Moreover, previous research shows associations with demographic factors, for example, age and sex. Here, we investigate the relevance of patients' psycho‐social profile for surgical decision‐making. Methods: We prospectively studied 296 patients from two large German epilepsy centers. Multiple logistic regression analyses were used to investigate variables linked to neurologists' recommendations for and patients' acceptance of surgery or intracranial video‐electroencephalographic monitoring. Patients' psycho‐social profiles were assessed via self‐reports and controlled for various clinical–demographic variables. Model selection was performed using the Akaike information criterion. Results: As expected, models for neurologists' surgery recommendations primarily revealed clinical factors such as lateralization and localization of the seizure onset zone, load with antiseizure medication (ASM), and site of the epilepsy‐center. For this outcome, employment was the only relevant psycho‐social aspect (odds ratio [OR] = .38, 95% confidence interval [CI] = .13–1.11). In contrast, three of the five relevant predictors for patients' acceptance were psycho‐social. Higher odds were found for those with more subjective ASM adverse events (OR = 1.04, 95% CI = .99–1.00), more subjective seizure severity (OR = 1.12, 95% CI = 1.01–1.24), and lower subjective cognitive impairment (OR = .98, 95% CI = .96–1.00). Significance: We demonstrated the relevance of the patients' psycho‐social profile for decision‐making in epilepsy surgery, particularly for patients' decisions. Thus, in addition to clinical–demographic variables, patients' individual psycho‐social characteristics add to the understanding of surgical decision‐making. From a clinical perspective, this calls for individually tailored counseling to assist patients in finding the optimal treatment option.